On the positron superthermality and ionic masses contributions on the wave behaviour in collisional space plasma. Issue 2 (15th July 2020) - Abdelwahed, H.G.; Sabry, R.; El-Rahman, A.A.
Highlights: Damped structures with critical behaviors in a four-component plasma fluid having positive and negative ions, non-thermal distributed positrons and electrons have been examined for related Earth's ionosphere plasma parameters. Effects of the positron density ratio, ionic mass ratio, electron density ratio, the index of non-thermality on the formation of both damped structures of compressive and rarefactive types are studied. The results performed in this work may be usable in the plasma of (D-F) Earth's ionosphere regions. Abstract: The damped solitary structure characteristics in plasma model contains two fluid ions refers to positive and negative pairs, superthermal positrons and electrons density distributions have been considered. The damped two dimensional Kadomtsev–Petviashvili (DKP) equation has been gained from the plasma model. The nonlinear conditions of critical DKP are studied for parameters concerning the ionosphere plasma of Earth's. Effects of the positron number ratio, ion masses ratio, electron number ratio, the superthermality index and frequency of collisional parameters on the figuration of both compressive and rarefactive damped structures are investigated. It is a prominence invokes to indicate that the produced results may be applicable in the space plasmas of (D-F) ionosphere of Earth's regions.